Docking Results - Pozzati, Gabriele; Kundrotas, Petras; Elofsson, Arne (Stockholm University, 2021)
Results for the study "Improved protein docking by predicted interface residues". Archive contains GRAMM roto-translations of Ligands around the original position of the Receptor. Several set of docking models have been produced considering different set of protein interface constraintsto score GRAMM roto-translations. Also, AACE18 scoring function results are included. For every docking model, DockQ score has been calculated comparing with both bound and unbound native structures. Find detailed methods at https://www.biorxiv.org/content/10.1101/2021.08.25.457642v1
Keywords: Bioinformatics and computational biology not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi)